Anxiety and Its Association With Screening Mammography. Issue 3 (30th April 2021) - Loving, Vilert A; Aminololama-Shakeri, Shadi; Leung, Jessica W T
Abstract: Anxiety is often cited as a risk of screening mammography, and organizations such as the U.S. Preventive Services Task Force list anxiety as a screening-associated "harm" that should be mitigated. However, the level of mammography-related anxiety risk is difficult to assign clearly for myriad reasons, including the variability of individuals' baseline susceptibility to anxiety, the self-reported nature of subjective anxiety states, and the multiple sources of breast cancer screening–related anxiety. In addition, anxiety measures differ between studies and psychological responses to screening mammography vary across racial and ethnic groups. Nonetheless, breast radiology practices should acknowledge the existence of mammography-associated anxiety and consider strategies to decrease it. These strategies include immediate screening interpretations, patient education efforts, and relaxation techniques.